Pengaruh Counterpoise Terhadap Sambaran Petir Yang Menyebabkan Back-Flashover Menggunakan Matlab R2016a Pada Sutt 150 Kv Koto Panjang-Garuda Sakti - Yosefa Riani; Suwitno Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Indonesia is a country in a tropical climate where the number of highlightning days per year is high. Transmission lines are one of the systems often affected by lightning disturbances directly or indirectly by lightning stroke. In this paper to minimize the occurrence of these disturbances, a lightning strike protection system is needed by using one or two grounding wires installed above the phase wire, this ground wire is grounded through the tower body by using a counterpoise grounded a few meters below the tower footing. Then, the simulation is running using the MATLAB r2016a Syntax to reduce the cross-arm voltage then minimize the back-flashover by increasing the size of the grounding electrode. The simulation result shows that the value of crossarm voltage is 2056,1 kV with a resistance value is 9,8 Ohm causes back-flashover. Then the electrode size was added so that the resistance value changed to 5.32 Ohm and the crossarm voltage value decreased by 1323.4 kV so that back-flashover could be minimized.Keywords: Direct Stroke, Counterpoise, Back-flashover